2017
DOI: 10.1039/c7nr03129g
|View full text |Cite
|
Sign up to set email alerts
|

Carrier-free, self-assembled pure drug nanorods composed of 10-hydroxycamptothecin and chlorin e6 for combinatorial chemo-photodynamic antitumor therapy in vivo

Abstract: Carrier-free nanodrugs formulated from supramolecular self-assembly of pure drug molecules have emerged as an innovative and promising strategy for tumor therapy. We report herein a new and simple method to directly assemble a small hydrophobic anticancer drug 10-Hydroxycamptothecin (HCPT) with a photosensitizer Chlorin e6 (Ce6) to form stable, discrete nanorods (NRs), which not only circumvent the extreme hydrophobicity of HCPT but also incorporate two different modalities into one delivery system for combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(72 citation statements)
references
References 64 publications
1
71
0
Order By: Relevance
“…Studies have shown that oxidative stress produced by nanomaterials can be observed in multiple cell types. 29 The ROS can be visualized to determine the oxidative stress levels in cells with or without GONs pretreatment after X-ray irradiation using DCFH-DA as a fluorometric probe. 30 The normalized fluorescence intensities of the studied cells are shown in Figure 4C-E.…”
mentioning
confidence: 99%
“…Studies have shown that oxidative stress produced by nanomaterials can be observed in multiple cell types. 29 The ROS can be visualized to determine the oxidative stress levels in cells with or without GONs pretreatment after X-ray irradiation using DCFH-DA as a fluorometric probe. 30 The normalized fluorescence intensities of the studied cells are shown in Figure 4C-E.…”
mentioning
confidence: 99%
“…Chlorin e6 (Ce6) is a second-generation photosensitizer, synthesized from chlorophyll. Upon light irradiation by light in the red spectrum (655 nm), the activated Ce6 could efficiently generate 1 O 2 [ 82 ]. Moreover, there exist obvious clinical benefits achieved by the Ce6-mediated PDT on various cancer treatments, such as bladder cancer, melanoma and nasopharyngeal cancer.…”
Section: Representative Applications Of Cargo-free Nanomedicinementioning
confidence: 99%
“…Therefore, various kinds of cargo-free nanomedicines composed of Ce6 have been developed for chemo–photodynamic combination therapy. For example, Liang’s group employed a green and simple reprecipitation method to form stable carrier-free pure nanodrugs (PNDs) consisting of Ce6 and HCPT [ 82 ]. Based on their results, it has been found that the ROS-generation efficiency of Ce6 and the cytotoxicity of HCPT were not influenced during the co-self-assembly process.…”
Section: Representative Applications Of Cargo-free Nanomedicinementioning
confidence: 99%
“…Some of them even reach up to 100%. [19][20][21] Besides, the drug loading ratio of small molecule nanodrugs is precise and tunable because of the well-defined structure of small molecules and cocktail self-assembly process. 22 And there is no concern on carrier-induced longterm toxicity for avoiding the use of additional carriers.…”
Section: Introductionmentioning
confidence: 99%